Pengaruh Digitalisasi Layanan terhadap Kepuasan Nasabah pada PT Bank Sumsel Babel Cabang Pembantu Pulau Beringin Kabupaten Ogan Komering Ulu Selatan - Oci Lian Fernandes; Nova Tri Eriani; Dismita Citra Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of service digitalization on customer satisfaction at PT. Bank Sumsel Babel, Pulau Beringin Sub-Branch, Ogan Komering Ulu Selatan Regency. The research was conducted as part of the requirements to obtain a Bachelor's degree in Economics at the Faculty of Islamic Economics and Business (FEBI), Institut Agama Islam Pagar Alam. The results indicate that service digitalization has a positive and significant effect on customer satisfaction. This is supported by statistical analysis, where the t-value (1.699) exceeds the t-table value (1.117), and the significance level is 0.000 < 0.05. The beta coefficient of 0.954 shows that digitalization influences customer satisfaction by 95.4%. However, the correlation coefficient (R) is 0.268, and the coefficient of determination (R Square) is 0.072, indicating a relatively low overall influence. Despite this, digital services still play an important role in shaping customer satisfaction. Key influencing indicators include efficiency, reliability, fulfillment, privacy, responsiveness, and contact, alongside product quality, service quality, emotional factors, and cost. The study recommends enhancing digital service quality to improve customer satisfaction more effectively.